First report of a cricket with filiform hairs on foretibia (Orthoptera: Gryllidae: Gryllinae) - Liu, Yi-Jiao; He, Zhu-Qing (Zootaxa, 2022)
There are hundreds of filiform mechanosensory hairs on the cricket cercus, however, such sensory hairs have never been reported on cricket foretiba. In this study, we collected a new species from China, which possesses two long filiform hairs on foretibia. Combined with its burrowing habit, these hairs mainly contribute to detecting ground vibration. We describe a new genus for this new species Fodigryllus bisetus gen. et sp. nov. The type specimens are deposited in the Museum of Biology, East China Normal University (ECNU).